Deindustrialization paths and growth models: Germany and Spain in comparative perspective - Miguel Angel Casau; Daniel Herrero (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
This paper investigates the deindustrialization process in Germany and Spain from 1995 to 2018. It is argued that the deindustrialization trajectories of each country are partially related to their growth models. An analysis in two steps is conducted. First, using the OECD input-output tables, a Hierarchical Structural Decomposition Analysis is applied, and the variation in the manufacturing value-added share is decomposed into five deindustrialization drivers: income, investment, relative prices, outsourcing and globalization. Second, building on the growth model perspective, an interpretative framework to analyze the evolution of the five abovementioned drivers is presented. The interaction between institutions, aggregate demand and the economic structure is explicitly considered in this framework. The comparative study of the German and Spanish cases and the distinction between the pre- and post-crisis periods illustrates the consequences of the distinct growth models (and the economic policies on which they are grounded) on structural change. The results suggest that the evolution of the deindustrialization drivers (and thus the manufacturing value-added share) in both countries is well-explained by their specific fiscal, labor, and industrial policies.
Keywords: E12; E25; P16; C67; O14; 330; deindustrialization; growth models; input-output analysis; macroeconomic policies; industrial policy